The development of a novel model for mining method selection in a fuzzy environment; case study: Tazareh Coal Mine, Semnan Province, Iran (Rudarsko-geološko-naftni zbornik, 2017)
Mining method selection (MMS) for mineral resources is one of the most significant steps in mining production management. Due to high costs involved and environmental problems, it is usually not possible to change the coal mining method after planning and starting the operation. In most cases, MMS can be considered as an irreversible process. Selecting a method for mining mainly depends on geological, geometrical properties of the resource, environmental impacts of exploration, impacts of hazardous activities and land use management. This paper seeks to develop a novel model for mining method selection in order to achieve a stable production rate and to reduce environmental problems. This novel model is illustrated by implementing for Tazareh coal mine. Given the disadvantages of the previous models for selecting coal mining method, the purpose of this research is modifying the previous models and offering a comprehensive model. In this respect, TOPSIS method is used as a powerful multi attribute decision-making procedure in Fuzzy environment. After implementation of the presented model in Tazareh coal mine, long wall mining method has been selected as the most appropriate mining method.